2017
DOI: 10.1111/2041-210x.12777
|View full text |Cite
|
Sign up to set email alerts
|

Identifying targets and agents of selection: innovative methods to evaluate the processes that contribute to local adaptation

Abstract: Summary Extensive empirical work has demonstrated local adaptation to discrete environments, yet few studies have elucidated the genetic and environment mechanisms that generate it. Here, we advocate for research that broadens our understanding of local adaptation beyond pattern and towards process. We discuss how studies of local adaptation can be designed to address two unresolved questions in evolutionary ecology: Does local adaptation result from fitness trade‐offs at individual loci across habitats? How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 102 publications
(185 reference statements)
3
103
0
Order By: Relevance
“…Theoretical models (Dieckmann & Doebeli, ; Hedrick, ; Hedrick, Ginevan, & Ewing, ; Levene, ) and studies in key model systems (Abzhanov, Protas, Grant, Grant, & Tabin, ; Barrett, Rogers, & Schluter, ; Hoekstra et al., ) have suggested trade‐offs at individual loci (e.g., antagonistic pleiotropy) to be common. However, field reciprocal transplant experiments and experimental evolution studies have often found a pattern of conditional neutrality, where loci have a strong effect on fitness in one environment but have an undetectable effect on fitness in alternative environments (reviewed in Bono, Smith, Pfennig, & Burch, ; Wadgymar et al., ). This pattern has also been found in the coastal perennial/inland annual M. guttatus system, where three salt tolerance QTLs have fitness effects in coastal habitat but no detectable effects in inland habitat (Lowry et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical models (Dieckmann & Doebeli, ; Hedrick, ; Hedrick, Ginevan, & Ewing, ; Levene, ) and studies in key model systems (Abzhanov, Protas, Grant, Grant, & Tabin, ; Barrett, Rogers, & Schluter, ; Hoekstra et al., ) have suggested trade‐offs at individual loci (e.g., antagonistic pleiotropy) to be common. However, field reciprocal transplant experiments and experimental evolution studies have often found a pattern of conditional neutrality, where loci have a strong effect on fitness in one environment but have an undetectable effect on fitness in alternative environments (reviewed in Bono, Smith, Pfennig, & Burch, ; Wadgymar et al., ). This pattern has also been found in the coastal perennial/inland annual M. guttatus system, where three salt tolerance QTLs have fitness effects in coastal habitat but no detectable effects in inland habitat (Lowry et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important forces driving the evolution of ecological specialization and the origin of biodiversity is local adaptation (Clausen, ; Colosimo et al., ; Sobel, Chen, Watt, & Schemske, ). Local adaptation is characterized by reciprocal home‐site advantage, whereby populations perform best in their home habitat while performing poorly in foreign habitats (Hereford, ; Hoekstra, Hirschmann, Bundey, Insel, & Crossland, ; Kawecki & Ebert, ; Wadgymar et al., ). Numerous reciprocal transplant experiments have identified locally adapted populations (Leimu & Fischer ; Hereford, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in climatic, edaphic, and abiotic agents of selection across space can favor the evolution of local adaptation, such that ecotypes have enhanced performance in their home sites and reduced fitness in contrasting environments (Kawecki and Ebert, 2004). Disentangling the causal agents of local adaptation remains challenging because multiple interacting factors can contribute to fitness trade-offs across environments (Lowry et al, 2008;Wadgymar et al, 2017b). In some systems, variation in climatic factors has been directly linked to local adaptation (Liancourt et al, 2013;Anderson and Wadgymar, 2020).…”
mentioning
confidence: 99%
“…Studies have been able to leverage ‘omics’ technologies in the field to study the basis of local adaptation (Knight et al ., ; Gould et al ., ) and contribute to the understanding of changing environmental conditions and climate change (Fournier‐Level et al ., ; Hancock et al ., ; Nagano et al ., ; Plessis et al ., ; D'Agui et al ., ). Experiments that manipulate agents of selection in native field environments using pedigreed populations or GWAS panels also offer unique opportunities for detecting the genetic and environmental mechanisms that generate local adaptation (Wadgymar et al ., ). Combinatorial, multi‐location experimental set‐ups and reciprocal transplant experiments can unlock fitness‐associated loci relative to climate, macro‐ and microbiota, and local adaptation (Wilczek et al ., ; Fournier‐Level et al ., ; Agrawal et al ., ; Prasad et al ., ; Züst et al ., ; Wagner et al ., ; Brachi et al ., ).…”
Section: The Eefg Research Program: Exploiting Variationmentioning
confidence: 97%